PENGARUH VARIASI KONSENTRASI NATRIUM HIDROKSIDA TERHADAP SIFAT FISIK SEDIAAN SABUN PADAT EKSTRAK DAUN NANGKA (Artocarpus heterophyllus Lam.) - Mikhania Christiningtyas Eryani; Hadi Barru Hakam Fajar Siddiq; Asa Falahi; Noer Layla Fitri Ani (MEDFARM: Jurnal Farmasi dan Kesehatan, 2023)
The aim of this study was to determine the variataion concentration effect of sodium hydroxide (NaOH) on the physical properties of jackfruit leaf extract solid soap (Artocarpus heterophyllus Lam.). The concentration of NaOH used were 2.5% (F1); 5% (F2) and 7.5% (F3). The physical evaluation was carried out in the form of an organoleptic test, homogeneity test, pH test, water content test, and foam height test. The results showed that variations in NaOH concentration had no effect on the organoleptic physical properties (odor, shape, color) and homogeneity of solid soap but had an effect on the physical properties of pH, water content, and foam height of solid soap